Safety of COVID-19 vaccines in patients with immunoinflammatory rheumatic diseases (preliminary data) - A. N. Kulikov; N. V. Muravyeva; B. S. Belov (Современная ревматология)
Objective: to assess the safety of COVID-19 vaccines in patients with immunoinflammatory rheumatic diseases (IRD) in real clinical practice.Patients and methods. A cross-sectional study of patients with IRD, who were admitted to V.A. Nasonova Research Institute of Rheumatology for inpatient or outpatient treatment. All patients received at least 1 dose of vaccine against COVID-19 (main group). The control group consisted of vaccinated persons without IRD. All participants were interviewed by the researcher by filling out a unified questionnaire, additional information was obtained from medical records.Results and discussion. The study included 204 patients with IRD (151 of them were vaccinated with Sputnik V, 31 with Sputnik Light, 19 with СoviVac, 3 with EpiVacCorona; 173 patients received the second component of vaccine) and 131 subjects without IRD (101 of them were vaccinated with Sputnik V, 17 – CoviVak, 5 – Sputnik Light, 2 – EpiVacCorona, 6 – Pfizer/BioNTech; 124 patients received the second component of the vaccine). The number of patients with IRD who had both local and systemic reactions after administration of the first component of the vaccine was significantly less than in the control group (19.6 and 38.9%, respectively; p<0.001). Similar differences were noted after the administration of the second component (15.6 and 27.4%, respectively; p=0.013). Adverse events (AEs) such as pain at the injection site without restriction of movement, weakness, fever, arthralgia/myalgia and chills were significantly more common in the control group after the administration of the first component of the vaccine. After complete immunization, AEs were absent in 35.8% of patients with IRD and in 21% of controls (p=0.006). Exacerbations of IRD and new autoimmune phenomena were not registered in any case.Conclusion. According to preliminary data, vaccination against COVID-19 in patients with IRD appears to be quite safe. Further studies are needed to investigate the safety, immunogenicity, and clinical efficacy of COVID-19 immunization in rheumatic patients.